The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s12265-021-10158-0
|View full text |Cite
|
Sign up to set email alerts
|

Venoarterial Extracorporeal Membrane Oxygenation for Acute Massive Pulmonary Embolism: a Meta-Analysis and Call to Action

Abstract: Venoarterial extracorporeal membrane oxygenation (ECMO) has been used to treat acute massive pulmonary embolism (PE) patients. However, the incremental benefit of ECMO to standard therapy remains unclear. Our meta-analysis objective is to compare in-hospital mortality in patients treated for acute massive PE with and without ECMO. The National Library of Medicine MEDLINE (USA), Web of Science, and PubMed databases from inception through October 2020 were searched. Screening identified 1002 published articles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Despite significant disease severity, the 77.7% 90‐day survival rate observed for our series is improved compared to prior studies involving VA‐ECMO in PE patients 13–15 . VA‐ECMO allows bypass of both cardiac and pulmonary circulation by providing key hemodynamic and respiratory support.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Despite significant disease severity, the 77.7% 90‐day survival rate observed for our series is improved compared to prior studies involving VA‐ECMO in PE patients 13–15 . VA‐ECMO allows bypass of both cardiac and pulmonary circulation by providing key hemodynamic and respiratory support.…”
Section: Discussionmentioning
confidence: 59%
“…Despite significant disease severity, the 77.7% 90-day survival rate observed for our series is improved compared to prior studies involving VA-ECMO in PE patients. [13][14][15] VA-ECMO allows bypass of both cardiac and pulmonary circulation by providing key hemodynamic and respiratory support. While previously used as a standalone therapy for support or to allow time for systemic thrombolysis, consideration must be given to combination therapy with LBT.…”
Section: Discussionmentioning
confidence: 99%
“…As in many interventions, the timing of ECMO onset is of utmost importance. Indeed, survival rates were constantly significantly higher when ECMO was implanted for PE-associated cardiogenic/obstructive shock compared to during E-CPR [ 7 , 9 , 31 , 33 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 53 , 54 , 55 ] ( Figure 1 ). For instance, Meneveau et al observed a survival rate of 11% in high-risk PE patients undergoing E-CPR as compared to an overall survival rate of 52% for patients on ECMO for cardiogenic shock [ 7 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Similarly, the survival rate was only 9% in patients with PE on E-CPR whereas it was 42% when ECMO was initiated for refractory cardiogenic shock [ 45 ]. A recent meta-analysis confirmed that physicians tend to use ECMO as a rescue last-stage therapy, especially in PE [ 53 , 56 ]. Among 327 high-risk PE patients from 17 studies, ECMO was implanted for refractory cardiogenic shock in 140 (43%) patients and 187 (57%) patients for cardiac arrest [ 56 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In critically ill PE patients, veno-arterial extracorporeal membrane oxygenation (VA ECMO) could be applied for life-saving support. Indeed, ECMO is commonly utilized as an important strategy before surgical embolectomy (19).…”
Section: Indications For Surgerymentioning
confidence: 99%